Sox8 and Sox10 jointly maintain myelin gene expression in oligodendrocytes. Issue 2 (11th October 2017) - Turnescu, Tanja; Arter, Juliane; Reiprich, Simone; Tamm, Ernst R.; Waisman, Ari; Wegner, Michael
Abstract: In Schwann cells of the vertebrate peripheral nervous system, induction of myelination and myelin maintenance both depend on the HMG‐domain‐containing transcription factor Sox10. In oligodendrocytes of the central nervous system, Sox10 is also essential for the induction of myelination. Its role in late phases of myelination and myelin maintenance has not been studied so far. Here, we show that these processes are largely unaffected in mice that lack Sox10 in mature oligodendrocytes. As Sox10 is co‐expressed with the related Sox8, we also analyzed oligodendrocytes and myelination in Sox8‐deficient mice. Again, we could not detect any major abnormalities. Expression of many myelin genes was only modestly reduced in both mouse mutants. Dramatic reductions in expression levels and phenotypic disturbances became only apparent once Sox8 and Sox10 were both absent. This argues that Sox8 and Sox10 are jointly required for myelin maintenance and impact myelin gene expression. One direct target gene of both Sox proteins is the late myelin gene Mog . Our results point to at least partial functional redundancy between both related Sox proteins in mature oligodendrocytes and are the first report of a substantial function of Sox8 in the oligodendroglial lineage. Main Points: Myelin is maintained in the absence of Sox8 or Sox10. Sox8 and Sox10 are jointly required for myelin maintenance. Several myelin genes including Mog are common targets of Sox8 and Sox10.